The Government's Political Will in Optimizing MSME Empowerment in Bogowonto, Madiun - Muhamad Faik Khumaidi; Wahyu Anugrah Utama; Muhammad Chasan Amrulloh (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Empowering Micro, Small, and Medium Enterprises (MSMEs) is one of the main focuses of government policy in promoting inclusive and sustainable economic growth. In the Bogowonto area of ​​Madiun, government policy has been directed at optimizing the potential of MSMEs through various strategic programs and initiatives. This study aims to analyze government policies in optimizing MSME empowerment in Bogowonto, Madiun, and identify factors that influence the successful implementation of these policies. The research method used is a qualitative method with a descriptive-analytical approach. Data were obtained through in-depth interviews with MSME actors, local government officials, and local economic experts, as well as documentation studies from various secondary sources. The results show that government policies cover several key aspects, namely increasing access to capital, training and capacity building, and promotion and marketing of MSME products. This study also identifies several challenges in policy implementation, such as limited human resources, inadequate infrastructure, and a lack of awareness and active participation from MSME actors.